2010
DOI: 10.1007/s00213-010-2039-9
|View full text |Cite
|
Sign up to set email alerts
|

Extrasynaptic GABAA receptor activation reverses recognition memory deficits in an animal model of schizophrenia

Abstract: The present study shows that extrasynaptic GABA(A) receptors may present a novel target for the development of therapeutics aimed at improving cognitive deficits in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Moreover, the effects described at the 4 mg·kg -1 dose in the anxiety, rotarod and ethanol interaction tests are consistent with the profile of retigabine (Blackburn-Munro et al, 2005;Korsgaard et al, 2005). Recently, Damgaard et al (2011) have shown that AA29504 reverses recognition memory deficits in an animal model of schizophrenia, albeit retigabine is also effective in schizophrenia models (Sotty et al, 2009). …”
Section: In Vivo Propertiessupporting
confidence: 73%
“…Moreover, the effects described at the 4 mg·kg -1 dose in the anxiety, rotarod and ethanol interaction tests are consistent with the profile of retigabine (Blackburn-Munro et al, 2005;Korsgaard et al, 2005). Recently, Damgaard et al (2011) have shown that AA29504 reverses recognition memory deficits in an animal model of schizophrenia, albeit retigabine is also effective in schizophrenia models (Sotty et al, 2009). …”
Section: In Vivo Propertiessupporting
confidence: 73%
“…5-HT6 receptors are heteroreceptors, thought to modulate the release of multiple transmitters including dopamine, glutamate and acetylcho- (Marcos et al 2006). Conversely, upregulation of GABAergic transmission has also been shown to reverse the effects of PCP, again with a 1-min delay (Damgaard et al 2011). This is consistent with the increasing evidence suggesting that many of the deleterious effects of NMDA receptor antagonists may actually result from disinhibition of glutamatergic transmission (see 'GABA').…”
Section: Phencyclidine (Pcp)mentioning
confidence: 72%
“…PCP induces robust deficits in SOR with delays as short as 1 min (Grayson et al 2007;McLean et al 2009;Snigdha et al 2010;Sood et al 2010;Damgaard et al 2011;Arnt et al 2010) (but see Hashimoto et al 2005). This does mean, however, that effects on memory versus those on perceptual or motivational factors can be difficult to disentangle.…”
Section: Phencyclidine (Pcp)mentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, NOR has been listed by the TURNS initiative as relevant for studying visual learning and memory deficits in schizophrenia (TURNS.ucla.edu) and may be used to study cognitive deficits occurring in a range of disorders (Grayson et al, 2014). In our laboratory, we have extensively shown that sub-chronic phencyclidine (PCP) treatment impairs object recognition memory following a 1 min inter-trial interval-ITI (Damgaard et al, 2010(Damgaard et al, , 2011Grayson et al, 2007;Idris et al, 2010;McLean et al, 2009McLean et al, , 2011bSnigdha et al, 2010Snigdha et al, , 2011. We have also demonstrated the efficacy of a wide range of selective receptor targets to reverse these sub-chronic PCP-induced deficits (see for review) as have other labs using the same paradigm (see Meltzer et al, 2013 for review).…”
Section: Introductionmentioning
confidence: 99%